Regulasi Diri sebagai Prediktor Kecanduan Judi Online - Quroyzhin Kartika Rini; Ursa Majorsy; Rini Indryawati; Amaran Sidhiq (Asosiasi Dosen Muda Indonesia, 2025)
Online gambling addiction is a growing phenomenon that has serious psychological, social, and economic impacts on individuals. This behavior can trigger stress, interpersonal conflict, impaired self-control, and even significant financial losses. Self-regulation plays a role in guiding how individuals manage their urges, emotions, and behaviors, including their involvement in online gambling activities. This study involved 110 late adolescents aged 17–21 years as respondents. The instruments used included a self-regulation scale and an online gambling addiction scale. Data were analyzed using the Pearson Product Moment correlation technique. The results showed a positive and significant relationship between self-regulation and online gambling addiction in adolescents. These findings provide interesting insights into understanding online gambling addiction, particularly considering that self-regulation does not always function as a protective factor in the context of addictive behavior. In certain contexts, self-regulation can manifest in less adaptive forms and is actually associated with the continuation of addictive behavior.